THE EFFECT OF COATING TEMPERATURE AND PARTICLE SIZE ON THE BURNING TIME OF KEMPI SHELL BRIQUETTES - Vianus Ndopo Role, Narsisius; Murdiyanto, Danang; Crisanto Putra Mbulu, Bernardus (Mechanical, Energy and Material (METAL), 2024)
The current fuel is still sourced from fossil fuels, namely oil, coal and The current fuel is still sourced from fossil fuels, namely oil, coal and gas, which have many impacts on the environment. As an agricultural country located in the tropics, Indonesia is rich in biomass energy sources. In this research, the use of candlenut shells will be used or processed into alternative fuel, namely briquettes, with the aim of determining the value of combustion time and temperature produced through variations in composition and mesh size. The results of the research show that the effect of the burning temperature has an impact on the burning time of the briquettes and the resulting temperature, where the best burning time and temperature values ​​of the briquettes are produced by a burning temperature of 400°C with a grain size of 100 mesh, namely 177 minutes with an average burning temperature briquettes 193.9°C.